2018
DOI: 10.1021/acs.molpharmaceut.8b00505
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Molecular Dynamics Simulations of a Fusidic Acid Nanosuspension for Simultaneously Enhancing Solubility and Antibacterial Activity

Abstract: The aim of the present study was to formulate a nanosuspension (FA-NS) of fusidic acid (FA) to enhance its aqueous solubility and antibacterial activity. The nanosuspension was characterized using various in vitro, in silico, and in vivo techniques. The size, polydispersity index, and zeta potential of the optimized FA-NS were 265 ± 2.25 nm, 0.158 ± 0.026, and -16.9 ± 0.794 mV, respectively. The molecular dynamics simulation of FA and Poloxamer-188 showed an interaction and binding energy of -74.42 kJ/mol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 114 publications
0
27
0
Order By: Relevance
“…An increase was observed in the concentration above ration 1:1; the particles sizes and PDI increased. It has been reported before that the stabilizing effect of surfactant decreases at high concentrations as the surfactant molecules tend to aggregate in to micelles rather than associating with lipidic molecules [ 52 , 63 ]. The optimized drug-loaded quatsomes (VCM-StBAclm-Qt 1 ) had MHD, and PDI of 122.9 ± 3.78 nm and 0.169 ± 0.02, respectively, at physiological pH 7.4 ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…An increase was observed in the concentration above ration 1:1; the particles sizes and PDI increased. It has been reported before that the stabilizing effect of surfactant decreases at high concentrations as the surfactant molecules tend to aggregate in to micelles rather than associating with lipidic molecules [ 52 , 63 ]. The optimized drug-loaded quatsomes (VCM-StBAclm-Qt 1 ) had MHD, and PDI of 122.9 ± 3.78 nm and 0.169 ± 0.02, respectively, at physiological pH 7.4 ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al (2016) reported that, cefixime nanoparticles exhibited better antibacterial activity than pure cefixime against S. aureus and E. coli by agar well diffusion method [27]. Omolo et al (2018) demonstrated that antibacterial activities of different nanosuspension formulations of fusidic acid delivered through poloxamer 188 were found better as compared to pure fucidic acid [28]. Further, it was revealed that both in-vitro and in-vivo test of CA amorphous ultrafine particles by high gravity anti-solvent precipitation (HGAP) technique possessed better dissolution rate and stronger antibacterial activity by agar dilution method against S. aureus and E. coli [29].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-and nano-carrier systems are among the approaches that have been successfully utilized for encapsulation of various types of drugs such as peptides, proteins, and low-molecular weight drugs [3][4][5]. These systems have been found to overcome limitations of conventional dosages forms such as improving solubility [6], bioavailability, and biodistribution of drugs [7], and targeting disease sites [8], hence contributing to a high proportion of the active drug reaching the targeted site. In addition, drug carrier systems protect the loaded drugs from premature degradation in the biological environment, thus enhancing bioavailability and cellular uptake.…”
Section: Introductionmentioning
confidence: 99%